Analisis Kelayakan Usaha Home Industri Emi Craft Di Kota Medan - Romadon, Muhammad; Puspita, Riana; Hasibuan, Yetti Meuthia (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
Feasibility analysis is the first step in knowing MSMEs. Emi Craft's business is engaged in the creative economy industry. This researcher aims to analyze the feasibility of the Emi Craft Home Industry bracelet accessories business in Medan City. Investment appraisal method criteria include Payback Period (PP), Profitability Index (PI) and Break Event Point (BEP). Based on the results of the Payback Period (PP) of 25 days for the investment return time and the Profitability Index (PI) value > 1, the results obtained are 14.1, and the results of the break-even point (BEP) in the unit are 1,923 pcs, and the BEP price is Rp. 153,840,000. So, it can be concluded that the bracelet accessories business at the Emi Craft Home Industry in Medan City is feasible to run.